Relationship between the prevalence and severity of non‐alcoholic fatty liver disease and coronary artery disease: Findings from a cross‐sectional study of a referral center in northeast Iran. Issue 5 (27th April 2022) - Gholoobi, Arash; Gifani, Mehrnoosh; Gholoobi, Aida; Akhlaghi, Saeed; Pezeshki Rad, Masoud; Baradaran Rahimi, Vafa
Abstract: Background and Aim: Non‐alcoholic fatty liver disease (NAFLD) is becoming increasingly prevalent worldwide, and cardiovascular diseases are the most common cause of death in NAFLD patients. The present study aimed to evaluate the possible relationship between the presence and severity of NAFLD and coronary artery disease (CAD). Methods: A cross‐sectional study was conducted on 296 patients (122 men and 174 women, with mean age 54.10 ± 9.33 years) referred to the catheterization laboratory of Imam Reza Hospital affiliated to the Mashhad University of Medical Sciences, Mashhad, Iran, for elective coronary angiography to investigate the presence and severity of CAD. Additionally, all patients underwent abdominal ultrasonography (USG) to detect NAFLD and its severity. Results: Among the 296 patients, 187 (63.2%) had CAD and 160 (50.1%) had NAFLD. NAFLD patients had significantly higher prevalence of obesity (odds ratio [OR] = 1.047, 95% confidence interval [CI] = 1.002–1.094), hypertension (OR = 1.909, 95% CI = 1.027–3.55), hyperlipidemia (OR = 3.474, 95% CI = 1.862–6.482), and CAD (OR = 2.009, 95% CI = 1.100–3.669). The percentage of patients with normal vessels was higher in the non‐NAFLD group, followed by the group with mild and severe NAFLD ( P  < 0.001). However, single‐ and multi‐vessel disease incidences among the non‐NAFLD, mild, and severe NAFLD groups were 36.1, 43.1, and 63.7%, respectively. Interestingly, the percentage of patients with two‐vessel stenosis was significantly higher in severe NAFLD patients than mild and non‐NAFLD patients ( P  < 0.001). Conclusion: The prevalence and severity of NAFLD were independently associated with CAD. Mild NAFLD was primarily observed among patients with normal and non‐obstructive coronary artery patients, while severe NAFLD was more frequent in extensive CAD patients with multi‐vessel disease. Abstract : Flowchart of the study.